Effect of ethanol in ultrasonic assisted extraction technique on antioxidative properties of passion fruit (Passiflora edulis) leaves - Mohamad Khairi Zainol,; Wong, Keat Yi; Zamzahaila Mohd Zin,; Khairil Shazmin Kamarudin,; Muhammad Danish-Daniel Abdullah,; Ng, Khai Shin; Hasmadi Mamat, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The leaves of Passiflora edulis (Passion fruit) traditionally used in American countries as a folk medicine to treat both anxiety and nervousness. They are rich in polyphenols which have been reported as natural antioxidants. In this study, five concentrations of ethanol (15%, 30%, 45%, 60% and 75%) were used in the extraction of P. edulis leaves extracted using ultrasonic-assisted technique. Ultrasonic-assisted solvent extraction is a method that uses high frequency mechanical vibration to increase the effectiveness of the desire compound to be dissolved into the solvent. The total phenolic content and total flavonoid content were determined in this study. Antioxidant capacity was assessed with FTC, TBA and DPPH. The highest extraction yield was obtained using water extraction. The extract obtained by 75% ethanol showed the highest antioxidant activity by DPPH (2,2- diphenyl-1-picrylhydrazyl) radical scavenging assay (85.17 ± 0.36%) and Ferric Thiocyanate (FTC) test where the absorbance obtained was 0.09 ± 0.00. The same extract also exhibited the highest flavonoids content (90.94 ± 0.15 mg QE/g sample). The extract obtained by 15% ethanol exhibited the highest antioxidant activity in Thiobarbituric acid (TBA) assay (56.22 ± 5.01%). Apart from that, the highest phenolic content was found in 60% ethanol (57.08 ± 0.29 mg GAE/g sample). These results indicate that the leaves of P. edulis could be a potential source of natural antioxidants which can be used in dietary applications.